Relationship between the Cervical Microbiome, HIV Status, and Precancerous Lesions - Cameron Klein (American Society for Microbiology, 2019)
ABSTRACT Nearly all cervical cancers are causally associated with human papillomavirus (HPV). The burden of HPV-associated dysplasias in sub-Saharan Africa is influenced by HIV. To investigate the role of the bacterial microbiome in cervical dysplasia, cytobrush samples were collected directly from cervical lesions of 144 Tanzanian women. The V4 hypervariable region of the 16S rRNA gene was amplified and deep sequenced. Alpha diversity metrics (Chao1, PD whole tree, and operational taxonomic unit [OTU] estimates) displayed significantly higher bacterial richness in HIV-positive patients (P = 0.01) than in HIV-negative patients. In HIV-positive patients, there was higher bacterial richness in patients with high-grade squamous intraepithelial lesions (HSIL) (P = 0.13) than those without lesions. The most abundant OTUs associated with high-grade squamous intraepithelial lesions were Mycoplasmatales, Pseudomonadales, and Staphylococcus. We suggest that a chronic mycoplasma infection of the cervix may contribute to HPV-dependent dysplasia by sustained inflammatory signals. IMPORTANCE HPV is known to be the causal agent in the majority of cervical cancers. However, the role of the cervical bacterial microbiome in cervical cancer is not clear. To investigate that possibility, we collected cervical cytobrush samples from 144 Tanzanian women and performed deep sequencing of bacterial 16S rRNA genes. We found that HIV-positive patients had greater bacterial richness (P = 0.01) than HIV-negative patients. We also observed that women with high-grade squamous intraepithelial lesions (HSIL) had greater cervical bacterial diversity than women with cytologically normal cervices. Data from our precise sampling of cervical lesions leads us to propose that Mycoplasma contributes to a cervical microbiome status that promotes HPV-related cervical lesions. These results suggest a greater influence of the bacterial microbiota on the outcome of HPV infection than previously thought.